Pozycja fundacji w sferze prowadzonej przez nią działalności leczniczej - Blicharz, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The Law on therapeutic activity provides the changes concerning both private and public sector of medical services. Those changes are relevant also for the position of foundations as non-government actors active on widely understood medical market. The foundations pursue an activity within the meaning of Article 3 of the Law on therapeutic activity, consisting in providing the therapeutic services or promoting the health or performing didactic or research tasks connected with providing therapeutic services — which creates the conditions to realize statutory tasks protection and promotion of health.
Keywords: fundacje; ochrona zdrowia; ustawa o działalności leczniczej; usługi medyczne